THE EFFECT OF COMPLEX SKILL EXERCISES ON SOME BIOCHEMICAL VARIABLES AND SPEED OF SKILL PERFORMANCE FUTSAL FOOTBALL - Hussein Abdul Ghaffar Jawad; Prof. Dr. Ammar Jasim Muslim (Scholars Digest Publishing, 2024)
The complex exercises in the game of futsal football are of great importance in changing the style of play, creating gaps, and penetrating competitors’ defense. At the same time, they have different repercussions on the biochemical variables, as each exercise has effects, perhaps positive or negative, according to the rules, properties, and features of that exercise and its psychological, physical, physiological, and physical content. The researchers believe that complex exercises have a positive impact on the internal environment of athletes. The problem of the research is that the researchers sought to prepare complex skill exercises, since the game of indoor football depends on the phosphate and lactic systems for the most part, which can be developed through these exercises through the complexity, speed, and difficulty of the exercise with Determine the performance time In addition to the great pressure due to the small area of the indoor football field and the large monitoring of the players, it requires improving the speed of performance, and it requires improving the physical and skill capabilities, which can be gained through the complex exercises prepared by the researchers. The researcher sought to prepare complex skill exercises for the players of Al-Shabab Al-Basri Futsal Club for the season (2023-2024). Identifying the differences between the chemical variables before and after performing the experimental variable for the research sample. The researchers assumed that complex skill exercises with the stomach have a positive effect on the research sample. There are also differences between the chemical variables before and after the performance of the experimental variable for the research sample. The researcher used the experimental method as it is the best method to solve the research problem most important conclusions were that the complex skill exercises had a positive role in developing the speed of skill performance, and this is what was indicated by the significant differences between the pre- and post-tests of the experimental group.
Keywords: complex skill exercises - biochemical variables - speed of skill performance.